A continuity of shari'a political authority and homicide in the nineteenth century - Wright, Brian (The American University in Cairo Press, 2023)
"In the second half of the nineteenth century, states across the Muslim World developed new criminal codes and reshaped their legal landscapes, laying the foundations of the systems that continue to inform the application of justice today. Influenced by colonialism and the rise of the modern state's desire to control their populations, many have seen the introduction of these codes as a pivotal shift and divergence from the Shariʼa, the dominant paradigm in premodern Muslim jurisdictions. In A Continuity of Shari'a, Brian Wright challenges this view, comparing between the Egyptian, Ottoman, and Indian contexts. By examining the environment in which the new codes were created, highlighting the work of local scholars and legal actors, and examining the content of the codes themselves, Wright argues that the criminal systems of the late nineteenth century have more connections to their past than previously understood. Colonial influence was adapted to local circumstances and synthesized with premodern understandings in an eclectic legal environment to create solutions to local problems while maintaining a continuity with the Shari'a."--